Literature Review - Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2016)
Small, rural and remote regions around the world are transforming due to forces outside of their control such as globalization, neoliberalism and climate change. While often characterized as being in a state of decline due to dwindling populations and employment opportunities, this literature review reveals that numerous small communities are finding ways to capitalize on these forces of change. The review focuses on regions similar to the Magdalen Islands – situated in the western world, shaped by colonial powers, and relatively well off. The common pattern found among the successful cases is a development approach that is internally focused, builds on existing assets (human, physical and intangible) and is scale appropriate with results that are, therefore necessarily unique to each community. These cases all include senior government support, especially in the form of funding, and in some instances, capacity building, that allows community members to carry the torch and take up the work of revitalizing their community in the ways they deem appropriate.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)